T2 Systemic insulin resistance without dysglycaemia impairs angiogenesis. (26th October 2016) - Mercer, BN; Walker, AMN; Warmke, N; Griffin, KJ; Pickering, C; Westerman, T; Soomro, T; Galloway, S; Mughal, R; Yuldasheva, NY; Wheatcroft, SB; Kearney, MT; et al.
Abstract : Introduction: Insulin resistant disorders, such as diabetes, are associated with impaired angiogenesis. Using mice haploinsufficient for the insulin receptor (IRKO), versus wild-type (WT) littermate controls, it is possible to define the impact of systemic resistance on vascular biology, independent of hyperglycaemia. Methods: Developmental retinal angiogenesis was defined in P5 mice. Pathological angiogenesis was studied in adult mice after induction of hind-limb ischaemia; limb perfusion was assessed 21 days later using laser Doppler and gastrocnemius muscle capillary density defined histologically. VEGF-induced angiogenesis was assessed in vitro using an aortic sprouting assay and a Matrigel lung endothelial cell tubulogenesis assay. Data are expressed as mean[SEM]; p < 0.05 is denoted by *. Results: IRKO exhibited reduced vascular branching complexity (1048 [17] versus 1199 [11] branches/mm 2 *), tip cell formation (18.3 [0.2] versus 21.1 [0.3] tip cells/mm), and NG2+ pericyte coverage (51.6 [0.9] versus 59.8 [1.4]% of endothelial cell area*) in the developing retina. Adult IRKO also demonstrated impaired recovery of limb perfusion (0.62 [0.07] versus 0.82 [0.06] ischaemic/non-ischaemic flux ratio*), associated with reduced capillary density (42.1 [4.3] versus 57.9 [3.3] capillaries/microscopic field*). qRT-PCR revealed a 3.2-fold greater* expression of VEGF-A in the ischaemic muscle of IRKO. Endothelial sprouts from the aortae of IRKO were less abundant (21.8 [2.4] versus 29.9 [2.2] sprouts*), and were shorter (847 [38] versus 1037 [39] µm*). IRKO endothelial cells produced fewer tubules in response to VEGF-A (14.3 [2.4] versus 27.5 [2.9] tubules/microscopic field*). Conclusion: Insulin resistance, without dysglycaemia, is associated with abnormal developmental and pathological angiogenesis, and impaired functional response to the pro-angiogenic growth factor VEGF-A. Further studies are required to define the mechanism.